Symmetric dimethylarginine is a stronger predictor of mortality risk than asymmetric dimethylarginine among older people with kidney disease. (May 2019) - Patel, Liyona; Kilbride, Hannah S; Stevens, Paul E; Eaglestone, Gillian; Knight, Sarah; L Carter, Joanne; Delaney, Michael P; Farmer, Christopher KT; Dalton, Neil; Lamb, Edmund J
Background: Circulating asymmetric dimethylarginine and symmetric dimethylarginine are increased in patients with kidney disease. Symmetric dimethylarginine is considered a good marker of glomerular filtration rate, while asymmetric dimethylarginine is a marker of cardiovascular risk. However, a link between symmetric dimethylarginine and all-cause mortality has been reported. In the present study, we evaluated both dimethylarginines as risk and glomerular filtration rate markers in a cohort of elderly white individuals, both with and without chronic kidney disease. Methods: Glomerular filtration rate was measured in 394 individuals aged >74 years using an iohexol clearance method. Plasma asymmetric dimethylarginine, symmetric dimethylarginine and iohexol were measured simultaneously using isotope dilution tandem mass spectrometry. Results: Plasma asymmetric dimethylarginine concentrations were increased ( P  < 0.01) in people with glomerular filtration rate <60 mL/min/1.73 m 2 compared with those with glomerular filtration rate ≥60 mL/min/1.73 m 2, but did not differ ( P  > 0.05) between those with glomerular filtration rate 30–59 mL/min/1.73 m 2 and <30 mL/min/1.73 m 2 . Plasma symmetric dimethylarginine increased consistently across declining glomerular filtration rate categories ( P  < 0.0001). Glomerular filtration rate had an independent effect on plasma asymmetric dimethylarginine concentration, while glomerular filtration rate, gender, body mass index and haemoglobin had independent effects on plasma symmetric dimethylarginine concentration. Participants were followed up for a median of 33 months. There were 65 deaths. High plasma asymmetric dimethylarginine ( P  = 0.0412) and symmetric dimethylarginine ( P  < 0.0001) concentrations were independently associated with reduced survival. Conclusions: Among elderly white individuals with a range of kidney function, symmetric dimethylarginine was a better marker of glomerular filtration rate and a stronger predictor of outcome than asymmetric dimethylarginine. Future studies should further evaluate the role of symmetric dimethylarginine as a marker of outcome and assess its potential value as a marker of glomerular filtration rate.